The use of financial technology in the agriculture sector - Craig McIntosh; Caio Scuarcialupi Mansini (Asian Development Bank Institute (ADBI), 2018)
The finance sector has a key role to play in allowing agriculture to contribute to economic growth and poverty reduction. A rapidly evolving technological landscape is opening up new possibilities to target and price credit, to share risk, and to harness information technology to expand agricultural productivity. At the same time, many obstacles are not technological, so it is important to look for strategic places where policy and investment can help to improve outcomes for agricultural households. Our analysis first situates agricultural finance in the Asian context, and then discusses the role of financial technology (FinTech) in driving new products in credit and risk markets. We examine linkages to mobile money, financial literacy, national identification systems, and blockchain technology. The paper concludes with a discussion of policy takeaways for FinTech in agriculture to promote growth, enhance financial inclusion, and improve regional economic integration.
Keywords: Q16; O16; O33; 330; financial technology; agriculture; credit; risk; financial literacy